2019
DOI: 10.3390/cancers11111670
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Bethesda Category AUS/FLUS in Our Microscopes: Three-Year-Experience and Cyto-Histological Correlation

Abstract: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) introduced a new category: Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance (AUS/FLUS) comprising of heterogenous lesions with a lesser degree of atypia. Its routine use is a bit controversial. The study cohort included AUS/FLUS thyroid cytopathological diagnoses signed out at Fimlab Laboratories from the period of 1 October 2013 to 31 December 2016. We analyzed all the AUS/FLUS cases, their cytology subclassific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…However, among these six categories of TBSRTC, further management is still complicated for the third category. 5 , 6 This category contains heterogeneous lesions assigned to two subgroups: atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS). 3–6 The prevalence of malignancy within this category ranges from 5% to 37%.…”
Section: Introductionmentioning
confidence: 99%
“…However, among these six categories of TBSRTC, further management is still complicated for the third category. 5 , 6 This category contains heterogeneous lesions assigned to two subgroups: atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS). 3–6 The prevalence of malignancy within this category ranges from 5% to 37%.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is slightly higher yet very similar to that reported by Eisa et al [33] with a malignancy rate of 74% in samples with nuclear/cytological atypia. Another study conducted by Huhtamella found that the rate of malignancy was almost the same for both nodules with architectural and cytological atypia, 12 and 12.4% respectively [34]. Among the malignant variants, papillary carcinoma was the most common diagnosis with a prevalence of 80.5% followed by NHL (1.5%) and medullary carcinoma (1.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The two indeterminate categories of III & IV are reported in the BSRTC definition report in about 15–30% and 25–40% of nodules respectively [ 16 , 17 ]. They pose clinical challenges for endocrine physicians [ 19 21 ]. While the majority will have benign nodules, the malignancy risk is not trivial and typically triggers for additional investigations or treatment [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%